Forkhead Domains of FOXO Transcription Factors Differ in both Overall Conformation and Dynamics - Psenakova, Katarina; Kohoutova, Klara; Obsilova, Veronika; Ausserlechner, Michael J; Veverka, Václav; Obsil, Tomas (Cells, 2019)
FOXO transcription factors regulate cellular homeostasis, longevity and response to stress. FOXO1 (also known as FKHR) is a key regulator of hepatic glucose production and lipid metabolism, and its specific inhibition may have beneficial effects on diabetic hyperglycemia by reducing hepatic glucose production. Moreover, all FOXO proteins are considered potential drug targets for drug resistance prevention in cancer therapy. However, the development of specific FOXO inhibitors requires a detailed understanding of structural differences between individual FOXO DNA-binding domains. The high-resolution structure of the DNA-binding domain of FOXO1 reported in this study and its comparison with structures of other FOXO proteins revealed differences in both their conformation and flexibility. These differences are encoded by variations in protein sequences and account for the distinct functions of FOXO proteins. In particular, the positions of the helices H1, H2 and H3, whose interface form the hydrophobic core of the Forkhead domain, and the interactions between hydrophobic residues located on the interface between the N-terminal segment, the H2-H3 loop, and the recognition helix H3 differ among apo FOXO1, FOXO3 and FOXO4 proteins. Therefore, the availability of apo structures of DNA-binding domains of all three major FOXO proteins will support the development of FOXO-type-specific inhibitors.
Keywords: Animals; protein FOXO3; Sequence Analysis, Protein; Hydrophobic and Hydrophilic Interactions; proteinové domény; lidé; Mice; Forkhead Box Protein O1; Protein Domains; forkhead transkripční faktory; myši; Models, Molecular; magnetická rezonanční spektroskopie; Forkhead Transcription Factors; Protein Structure, Secondary; molekulární modely; sekundární struktura proteinů; zvířata; Magnetic Resonance Spectroscopy; forkhead box protein O1; sekvenční analýza proteinů; Forkhead Box Protein O3; hydrofobní a hydrofilní interakce; Humans